POTENSI KOMODITI MANGGA GEDONG GINCU DALAM PENGEMBANGAN WILAYAH DAN PEREKONOMIAN KABUPATEN MAJALENGKA - Rita Herawaty Bangun (Jurnal Sosial Ekonomi Pertanian, 2020)
ABSTRACT The purpose of this research is to identify the location of the mango gedong gincu production base, the distribution characteristics and the role of mango gedong gincu commodity in support of regional development in the Majalengka Regency. The data used is a secondary data period of 2016-2018 years. The data analysis methods used are location quotient analysis, localization and specialization analyzers, basic service ratio analysis, and region multipliers. The results showed that the mango gedong gincu base area based on the production indicators in Majalengka District is Majalengka sub-district, Dawuan sub-district, Kasokandel sub-district, Panyingkaran sub-district, Kadipaten sub-district, Kertajapati subdistrict, Jatitujuh sub-district, Ligung sub-district, and Sumberjaya sub-district. The nine sub-districts consistently became the base of the mango gedong gincu commodity for a period of 2016 to 2018 years. Mango gedong gincu commodity farming is not concentrated on a sub-district but is spreading spatially and the mango commodity farming is not yet a specialized farming effort in the sub-district of the mango gedong gincu commodity base in Majalengka Regency. The presence of mango product farming promotes economic development in the form of a multiplier impact for the sub-districts of Majalengka in the form of an increase in community income and the absorption of manpower in agriculture and other sectors.. Keywords: base region, distribution characteristics, mango, multiplier effect